Numerical analysis of heat and mass transfer in micropolar nanofluids flow through lid driven cavity: Finite volume approach - Batool, Saima; Rasool, Ghulam; Alshammari, Nawa; Khan, Ilyas; Kaneez, Hajra; Hamadneh, Nawaf (Case studies in thermal engineering, 2022)
In this article, the heat and mass transfer mechanism of micropolar nanofluid embedded with Buoyancy force and magnetic field across an enclosure has been analyzed. Mass, energy, and momentum equations are required to construct the mathematical model to evaluate the efficacy of thermal performance of nanoparticles.The motivation for this study is to improve heat and mass transfer efficiency in heat transfer equipment and heat recovery units in industrial and engineering processes. Given the signification of dimensional analysis, 2D model is set up in their dimensionless context. In addition, the finite volume approach (FVM) is employed for numerical simulations. The thermophoresis and Brownian motion parameters has been considered for the temperature field, as proven via simulation. As a result of the random mobility of nanoparticles, more heat is emitted inside the enclosure. Furthermore, mass diffusivity and Schmidt number are inversely related,so that mass diffusion inside the cavity is faster for small values of Schmidt number. Additionally, it is discovered that a high vortex viscosity parameter produces a weak concentration field and has significant behavior when thermophoresis parameter and Reynolds number are significant. The simulations are captured in graphical form, and their results are explained in detail.